Survey, bioassay and greenhouse evaluation of selected botanical fungicides for the control of fungal diseases of mungbean (Vigna radiata (L.) R. Wilczek) - Telan, I.F.; Lapis, D.B. (1992)
Fresh concentrated crude extracts of 133 plant species were bioassayed in vitro for anti-fungal properties of which 18 selectively showed zones of inhibition against Diplodia natalensis Pole Evans, Sclerotium rolfsii Sacc., Rhizoctonia solani Kuhn, Colletotrichum lindemuthianum Brit. Cav., Fusarium oxysporum Schlect., Cercospora cruenta Ell. and Mart. and Pythium ultimum Trow. Allium sativum L. showed zones of inhibition against all test pathogens while Curcuma zedoaria (Berg.) Rosc. showed zones of inhibition against all test pathogens except S. rolfsii; A. cepa against S lindemuthianum; Polythea pendula Thwait against F. oxysporum and Zingiber officinale Roxc. against C. canescens and P. ultimum. Based on their greater zones of inhibition and stability, the above plant species were selected as the most promising plants with anti-fungal properties.

The concentrated crude extracts of the most promising plant species generally reduced their anti-fungal properties when subjected to high temperature and that supernatant portions of the respective extracts contain more anti-fungal properties when compared with their precipitants.

Used as foliar spray under greenhouse conditions, treatments with A. sativum and C. zedoaria against powdery mildew, Cercospora leafspot, anthracnose and Diplodia pod rot and A. cepa and T. rumphii against anthracnose had lesser disease ratings when compared with steriled distilled water control. The residual effects of the sprayed extracts generally showed fungicidal efficacy within one week of application
Keywords: Fungicides; Mungbean; Fungal diseases of plants -- Treatment